Phylogenetic Conflicts, Combinability, and Deep Phylogenomics in Plants. (20th November 2019) - Smith, Stephen A; Walker-Hale, Nathanael; Walker, Joseph F; Brown, Joseph W
Abstract: Studies have demonstrated that pervasive gene tree conflict underlies several important phylogenetic relationships where different species tree methods produce conflicting results. Here, we present a means of dissecting the phylogenetic signal for alternative resolutions within a data set in order to resolve recalcitrant relationships and, importantly, identify what the data set is unable to resolve. These procedures extend upon methods for isolating conflict and concordance involving specific candidate relationships and can be used to identify systematic error and disambiguate sources of conflict among species tree inference methods. We demonstrate these on a large phylogenomic plant data set. Our results support the placement of Amborella as sister to the remaining extant angiosperms, Gnetales as sister to pines, and the monophyly of extant gymnosperms. Several other contentious relationships, including the resolution of relationships within the bryophytes and the eudicots, remain uncertain given the low number of supporting gene trees. To address whether concatenation of filtered genes amplified phylogenetic signal for relationships, we implemented a combinatorial heuristic to test combinability of genes. We found that nested conflicts limited the ability of data filtering methods to fully ameliorate conflicting signal amongst gene trees. These analyses confirmed that the underlying conflicting signal does not support broad concatenation of genes. Our approach provides a means of dissecting a specific data set to address deep phylogenetic relationships while also identifying the inferential boundaries of the data set. [Angiosperms; coalescent; gene-tree conflict; genomics; phylogenetics; phylogenomics.]